Promoter effect of Pd species on Mn oxide catalysts supported on rare-earth-iron mixed oxide. Issue 21 (3rd October 2016) - Hosokawa, Saburo; Tada, Ryohei; Shibano, Takuya; Matsumoto, Shogo; Teramura, Kentaro; Tanaka, Tsunehiro
Abstract : The loading of a small amount of Pd species dramatically promotes a catalytic performance of MnO x species located on the hexagonal structure of YbFeO3 . Abstract : To replace or reduce the use of precious metals, novel guidelines for designing base metal catalysts, such as Mn or Fe, are greatly desired for various environmental cleanup reactions. Here we report a unique metamorphosis of MnO x by a small amount of Pd. For CO oxidation, the catalytic activity of amorphous MnO x species on hexagonal YbFeO3 (Mn-h-YbFeO3 ) is comparable to that of Pd catalysts such as Pd/Al2 O3, but loading a small amount of highly dispersed Pd on Mn-h-YbFeO3 drastically enhances its catalytic activity. The catalytic activity of 0.5 wt% Pd/Mn-h-YbFeO3 is exceptionally higher than that of 2.0 wt% Pd/Al2 O3, despite the lower Pd loading. The reduction behavior of the MnO x species, which are located on the ab plane of the hexagonal YbFeO3, is greatly changed by the loading of highly dispersed Pd, resulting in the dramatic lowering of the reduction temperature of MnO x . Thus, an extremely small amount of Pd species serves to promote the catalytic and reduction functions of the MnO x species on Mn-h-YbFeO3 . The establishment of such a promoter effect provides a guideline for decreasing the use of noble metal resources.